Water Pump Control System using Pulse Width Modulation Method Based on Arduino Uno R3 - Dani Usman; Dimas Surya Permana (Mekanika)
The availability of sufficient energy must support the rapid development of technology. The availability of electrical energy is decreasing. The saving of energy is one of the ways to solve this problem. One of the uses of electricity in clean water pumps, where clean water is the basic necessity of human life, therefore control system and auxiliary equipment is needed that is able to supply water according to the capacity of the need. However, often the use of the pump is not proportional to the capacity of the needs and the pump is often operated continuously, so that electricity and water are wasted. In this research, the use of water pumps is controlled, the rotation of the pump drive motor can be adjusted so that the pump output is in accordance with the water consumption load. The speed of a Direct Current (DC) motor is determined by the voltage. The higher the voltage, the faster the rotation. The focus of this research is to optimize the power efficiency of DC water pumps by using the Pulse Width Modulation (PWM) method to control the speed of the pump.